The hunger and the dusk. Volume 1 - Wilson, G. Willow, 1982- (IDW Publishing, a division of Idea and Design Works, LLC, 2024)
"In a decaying fantasy world, only humans and orcs remain--mortal enemies battling for territory and political advantage. But when a group of fearsome ancient humanoids known as the Vangol arrive from across the sea, the two struggling civilizations are forced into a fragile alliance to protect what they have built. As a gesture of his commitment to the cause--and to the relief of his bride-to-be, Faran Stoneback--the most powerful orc overlord, Troth Icemane, sends his beloved cousin Tara, a high-ranking young healer, to fight alongside brash human commander Callum Battlechild and his company of warriors. With a crisis looming, the success of this unlikely pair's partnership and the survival of their peoples will depend on their ability to unlearn a lifetime of antagonistic instincts toward one another ... and rise above the sting of hearbreak"--Provided by publisher.